2000
DOI: 10.1289/ehp.00108s123
|View full text |Cite
|
Sign up to set email alerts
|

Genetic susceptibility to lead poisoning.

Abstract: Major strides have been taken in the regulation of lead intoxication in the general population, but studies using genetic markers of susceptibility to environmental toxicants raise the question of whether genes can make certain individuals more vulnerable to environmental toxins such as lead. At least three polymorphic genes have been identified that potentially can influence the bioaccumulation and toxicokinetics of lead in humans. The first gene to be discussed in this review is the gene coding for delta-ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
105
1
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(112 citation statements)
references
References 86 publications
(80 reference statements)
2
105
1
4
Order By: Relevance
“…A polymorphism at position 177 leading to a G → C transversion results in occurrence of two alleles (ALAD-1 and ALAD-2) and three isozyme phenotypes, ALAD 1-1, ALAD 1-2, and ALAD 2-2. Studies have suggested that carriers of the ALAD-2 allele have higher blood lead levels (BLL) than ALAD-1 subjects and thus are more susceptible to lead toxicity [14][15][16]. 0304 Some authors suggest that the enhanced capacity of ALAD-2 to bind lead may confer resistance to its harmful effects because subjects with ALAD-2 may have less bio-available lead [15,17].…”
Section: Introductionmentioning
confidence: 99%
“…A polymorphism at position 177 leading to a G → C transversion results in occurrence of two alleles (ALAD-1 and ALAD-2) and three isozyme phenotypes, ALAD 1-1, ALAD 1-2, and ALAD 2-2. Studies have suggested that carriers of the ALAD-2 allele have higher blood lead levels (BLL) than ALAD-1 subjects and thus are more susceptible to lead toxicity [14][15][16]. 0304 Some authors suggest that the enhanced capacity of ALAD-2 to bind lead may confer resistance to its harmful effects because subjects with ALAD-2 may have less bio-available lead [15,17].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most studied genes that can affect the toxicity of Pb codes for d-aminolevulinic acid dehydratase (d-ALAD). d-ALAD is the second enzyme in the heme biosynthetic pathway and plays a role in the pathogenesis of Pb poisoning (Onalaja and Claudio 2000). When d-ALAD activity is deficient due to Pb poisoning, erythrocyte synthesis is inhibited, and blood hemoglobin concentrations decrease.…”
mentioning
confidence: 99%
“…In a study, in which knockout mice that lack the gene for HFE were used, an increase in transferrin saturation and iron storage in hepatocytes was observed (Waheed et al, 1999). In another study using HFE gene knockout mice, the expression of DMT-1 protein in the duodenum was found to be increased (Cantonwine et al, 2010;Onalaja and Claudio, 2000). The up-regulation of DMT-1 results in the increased absorption of iron and DMT-1 has affinity for several divalent cations such as lead and cadmium.…”
Section: Discussionmentioning
confidence: 99%